Influence of plant habitus traits on formation of seed productivity in flax - Tatiana Tovstanovska; Viktor Lyakh (Растениевъдни науки, 2024)
The studies were carried out at the Institute of Oilseed Crops of the National Academy of Agrarian Sciences of Ukraine in 2019/2020. The material of the study was interspecific hybrids of the second generation obtained in the system of dialel crosses with the participation of two wild annual homostylic species L. angustifolium and L. hispanicum with n = 15 and three accessions of cultivated flax: L 5 (Czech Republic), L 6 (India), M 32/2 (Ukraine). Correlation analysis of habitus traits of a flax plant with the number of bolls was carried out. As a result of studies between the height of the plant and the number of stems on the plant, there is no relationship; between the height of the plant with the number of lateral shoots and the number of bolls, weak and medium correlations, and sometimes their absence, were established (r = +0.218…+0.559; r = +0.253…+0.698, respectively). Medium and strong correlations were found between the number of stems on a plant with the number of side shoots and the number of bolls (r = +0.334…+0.892; r = +0.482…+0.818). Exceptionally strong and stable over the years correlations were observed between the number of lateral shoots on the plant and the number of bolls (r = +0.700…+0.922). The main trait of the habitus of a flax plant, which significantly affects the number of bolls on them, is the number of lateral shoots. This trait can be used as a reliable criterion for selecting plants for breeding for high seed productivity.